1963
DOI: 10.1161/01.res.13.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Tension and Stress in Man

Abstract: A method is described for calculating tension and stress acting within the wall of the left ventricle during the cardiac cycle. This method is based upon ventricular pressure observations and measurements of left ventricular dimensions and wall thickness made from biplane angiocardiograms. To calculate wall tension and stress, it is assumed that the left ventricle can be represented as an ellipsoid of revolution with a relatively thin wall. The relative importance of ventricular pressure, volume, shape and wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
1
1

Year Published

1965
1965
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(152 citation statements)
references
References 13 publications
6
144
1
1
Order By: Relevance
“…mean Pa, caused by a high SVR, which is in itself an adaptation to the perfusion requirements of the brain. Thus, although the thick ventricular wall resembles the pathophysiological changes during acquired ventricular hypertrophy in response to aortic stenosis or hypertension in humans (Grossman et al, 1975;Hood et al, 1968;Sandler and Dodge, 1963), there is no indication of the secondary myocardial fibrosis in giraffes that inevitably accompanies the acquired left ventricular hypertrophy observed in human disease. It is also noteworthy that newborn giraffes have a myocardial wall thickness relative to ventricular diameter that is similar to other mammals, such that the ventricular wall thickening seems to arise as mean Pa increases with neck length (Mitchell and Skinner, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…mean Pa, caused by a high SVR, which is in itself an adaptation to the perfusion requirements of the brain. Thus, although the thick ventricular wall resembles the pathophysiological changes during acquired ventricular hypertrophy in response to aortic stenosis or hypertension in humans (Grossman et al, 1975;Hood et al, 1968;Sandler and Dodge, 1963), there is no indication of the secondary myocardial fibrosis in giraffes that inevitably accompanies the acquired left ventricular hypertrophy observed in human disease. It is also noteworthy that newborn giraffes have a myocardial wall thickness relative to ventricular diameter that is similar to other mammals, such that the ventricular wall thickening seems to arise as mean Pa increases with neck length (Mitchell and Skinner, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Normal EF value X60% in healthy adults. End-systolic meridional wall stress (ESWS) was calculated using the Sandler -Dodge formula (Sandler and Dodge, 1963) for a thin-walled prolate ellipsoid: Stress (in kdynes cm À2 ) ¼ (1.333 Â SBP Â 2r)/h(2r þ h) where 1.333 is the conversion factor from mmHg to kdynes, SBP is the cuff systolic blood pressure, and r (radius; 2r ¼ LVEsD) and h (thickness) correspond to (systolic septal wall thickness þ systolic posterior wall thickness)/2.…”
Section: Cardiac Evaluationmentioning
confidence: 99%
“…Rediscovery of the ability of ventricular dilatation to increase wall stress in the 1950s, 11 along with renewed appreciation of the direct relationship between wall stress and myocardial energy expenditure, 12 stimulated measurements of systolic wall stress in patients with left ventricular overload caused by valvular heart disease. These studies demonstrated that overload-induced hypertrophy could normalize wall stress, [13][14][15] and so supported the then prevalent (and early 19th century) view that this proliferative response is largely beneficial. At the same time, however, the late 19th century view that overloadinduced hypertrophy shortens survival was confirmed by Meerson, who studied the clinical course in animals that had been subjected to experimental aortic banding.…”
Section: Beneficial and Deleterious Effects Of Overload-induced Hypermentioning
confidence: 53%